MENUMBUH KEMBANGKAN POTENSI MELALUI EKSTRAKURIKULER KALIGRAFI BAGI SISWA SD - Lia Nurmalia; Tajuddin Tajuddin; Nur Astuti Darmiyanti (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
GROWING POTENTIAL THROUGH CALLIGRAPHY EXTRACURRICULAR FOR ELEMENTARY SCHOOL STUDENTS This study aims to explore calligraphy extracurricular activities that can increase the interests, talents and potential of students. This study uses a descriptive method with a qualitative approach. To obtain research data, researchers used interview, observation, documentation, and literature studies, which were sourced from relevant books, previous research, school principals, PAI teachers, calligraphy trainers, and students at SDN Cimahi II, Klari District, Karawang. The results of the study prove that there is an increase in the ability of students in all aspects, both in terms of affective, cognitive and psychomotor through calligraphy extracurricular activities. In the process, the teacher plays an important role as a facilitator for the development of students' talents and interests, therefore this activity needs to be supported by conducive and pleasant conditions and atmosphere so that the process of this activity can realize achievements not only in the non-academic field (calligraphy art), but can develop towards academic achievement as well.